Culture and management techniques of Vietnamese Koi (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The first time study approach about culture and management in Bangladesh was conducted to observe the induce breeding, nursing and rearing technique of Vietnam koi (Anabas testudineus) fish culture in fresh water farm in Mymensingh region, Bangladesh for a period of 120 days from May, 2013 to August, 2013. In this study, inducing agent PG was used to achieve fertilization and hatching success of climbing perch, Anabas testudineus. During induce breeding, male and female in a ratio of 1:1 were used. The females were given single injection of 6-8 mg PG/kg body weight and the males were given 2-3 mg PG/kg body weight and nursing and rearing of vietnam koi (Anabas testudineus) fish were carried out as monoculture in earthen ponds.  In this study, two earthen ponds of 20 decimal with an average depth of 2.5 to 3 feet and two earthen ponds of 50 decimal with an average depth of 3 to 5 feet were used for nursing and rearing of Vietnam koi respectively. Nursing and rearing of Vietnam koi (Anabas testudinus) were carried out as monoculture in earthen ponds. The water temperature in the culture pond was ranged from 31.29±0.85 to 35.5±0.58 0C during nursing and rearing. The value of Dissolve Oxygen (DO) and pH was ranged from 6.20±0.41 to 5.0±0.71 mg/l and 7.8±0.62 to 7.1±0.47 respectively. The average weight of the fingerlings during stocking was 0.8g in nursery stage and 20g in rearing stage. Fingerlings were stocked at 1750 fish /decimal in the rearing pond. Fry in the nursing ponds were fed with Hatchery feed (powder) at the rate of 40-50% of their total body weight. Fingerlings in the rearing ponds were fed with Koi Starter and Koi Grower feed at the rate of 15-20% of their total body weight. The final average weight (g) of Vietnam koi was (0.8±0.08)g in nursery stage & (200.0±0.82)g in rearing stage. The Feed Conversion Ratio (FCR) of total artificial feed was 1.63. The survival rate of Vietnam koi fish was 70% and the net production was 167kg/decimal. The total benefit was 5,48,455.00 BDT. Benefit-cost ratio of this study was 1.43. Therefore, it could be concluded that nursing and rearing of Vietnam koi (Anabas testudineus) by using artificial feed under a monoculture system in the earthen ponds is potentially and economically feasible.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 93-105